Analysis of Maternal Religiosity, Parenting Style, and Social Support on the Value of Children with Autism: Educational Implications - Utami, Restu; Krisnatuti, Diah; Johan, Irni Rahmayani (FKIP Universitas Lampung, 2025)
Analysis of Maternal Religiosity, Parenting Style, and Social Support on Value of Children with Autism: Educational Implications. Objectives: This study examines the correlation and influence of maternal religiosity, parenting style, and social support on the value of children with Autism Spectrum Disorder (ASD), along with implications for their education. Methods: A total of 145 mothers of children with ASD from the Greater Jakarta area were purposively sampled. Data were collected through online questionnaires, analyzed using Spearman Rank correlation and Structural Equation Modeling (SEM). Findings: Most participants were millennial mothers with high educational attainment and stable economic status. High levels of religiosity, especially in personal religious practices, were reported, with family as the primary source of social support. Unexpectedly, correlation analysis revealed a negative association between maternal education level and value of children, although the children’s educational level was positively correlated with value of children. Although the authoritative parenting style emerged as the predominant approach, it did not exhibit a significant correlation with the perceived value of children. These findings highlight the crucial role of aligned maternal religiosity and adequate social support in shaping perceptions of children’s value. Conclusion: Highly educated mothers are negatively linked to perceived value of children, while children’s higher educational positively enhances their perceived value as symbols of autonomy and future potential. Therefore, strengthening maternal religiosity, family and community social support, and access to inclusive education are key to enhancing perceptions and educational outcomes for children with ASD. Keywords: autism, inclusive education, religiosity, social support, value of children.